GNAI3 inhibits tumor cell migration and invasion and is post-transcriptionally regulated by miR-222 in hepatocellular carcinoma. Issue 2 (28th January 2015) - Zhang, Yu; Yao, Jian; Huan, Lin; Lian, Junwei; Bao, Chuanyang; Li, Yan; Ge, Chao; Li, Jinjun; Yao, Ming; Liang, Linhui; He, Xianghuo
Abstract: Guanine nucleotide binding protein, alpha inhibiting activity polypeptide 3 (GNAI3) is involved in many biological processes. However, its biological function in hepatocellular carcinoma (HCC) remains unclear. An immunohistochemical staining analysis revealed that GNAI3 protein was down-regulated in HCC compared to non-cancerous liver. Furthermore, transwell assays indicated that GNAI3 inhibits HCC cell migration and invasion. Using software predictions and experimental screening, we found that miR-222 could directly bind to GNAI3 mRNA and decrease GNAI3 protein expression in HCC cells. Moreover, miR-222 was up-regulated in HCC and negatively correlated with GNAI3 protein expression. These results indicated that down-regulation of GNAI3 might be caused by up-regulation of miR-222 in HCC. In conclusion, GNAI3 was down-regulated by miR-222 in HCC, and this deregulation promoted migration and invasion of HCC. These findings extended our insight into the complex molecular mechanisms underlying the invasion and metastasis of HCC and may provide new therapeutic targets.